Nutritive value of palm oil sludge fermented with Aspergillus niger after stored in different packing materials - Pasaribu, T; Purwadaria, T; Sinurat, A.P; Rosida, J; Saputra, D.O.D (Indonesian Journal of Animal and Veterinary Sciences, 2001)
An experiment has been conducted to determine the effect of type of packaging and time of storage on fermented palm oil sludge. The palm oil sludge was fermented with Aspergillus niger, dried, kept in differentpackaging materials (plastic bags, feed bag, and paper bag) and stored under room temperatures for 12 weeks. The experiment was assigned in a split plot design (3x7). The parameters measured were water content, crude protein, soluble nitrogen, true protein, in vitro dry matter (IVDMD) and true protein digestibilities (IVTPD), total in vitro digestible protein, and the activities of mannanase and cellulase. Results showed that fermented palm oil sludge stored for 12 weeks increased the water content, decreased the true protein and fiber contents, and also reduced the activity of mannanase and cellulase and in vitro dry matter digestibility but no changes on the crude protein content, protein digestibility, and total digestible protein. It was concluded that fermented palm oil sludge should be kept in feed bag under room temperature if to be stored for 12 weeks. Â  Key words : Palm oil sludge, fermentation, nutritive value, storage